Identification and Management of Myofascial Trigger Points in Shoulder Pain: A Critical Narrative Review with Particular Reference to the Indian Clinical Context - Himanshu Devki Nandan Sharma; Geetanjali Bhatnagar; Pallav Bhatnagar (Asian Journal of Advanced Research and Reports, 2026)
Shoulder pain is a persistent and costly musculoskeletal complaint, and myofascial trigger points have been proposed as one of its principal peripheral contributors. The construct nevertheless remains contested. Palpation-based identification is imperfectly reproducible, instrumented alternatives remain investigational, and treatment trials frequently report short-lived analgesia obtained under conditions of incomplete blinding. These uncertainties acquire additional significance in India, where the occupational profile, the structure of rehabilitation services, patterns of out-of-pocket expenditure and pluralistic care-seeking shape both the presentation and the treatment of shoulder complaints in ways that international evidence does not capture. This critical narrative review evaluates the strength, coherence and transferability of evidence concerning the identification and management of myofascial trigger points in adults with shoulder pain, with explicit attention to the Indian setting. Literature was retrieved from six openly accessible scholarly sources, supplemented by citation and related-article searching, and appraised for design adequacy, measurement validity, risk of bias and contextual relevance rather than synthesised quantitatively. Four principal findings emerge. Occurrence estimates for trigger points in shoulder-related disorders are high but rest on small, largely uncontrolled samples with unstandardised case definitions. Diagnostic reproducibility is acceptable for composite features such as symptom recognition and referred sensation, yet poor for the taut band and the local twitch response, which remain the features most often taught. Instrumented measures, including pressure algometry and shear-wave elastography, discriminate trigger points from adjacent tissue at group level but have not been validated as patient-level diagnostic tests. Treatment effects for needling, compression, instrument-assisted mobilisation and electrophysical agents are consistently modest, short in duration and vulnerable to expectation effects, while the few trials designed to isolate a trigger-point-specific contribution have not confirmed one. Indian evidence is expanding but remains dominated by small single-centre trials in convenience samples, with limited representation of the occupational groups that carry most of the national burden. Priorities include diagnostic accuracy studies against defensible reference standards, adequately powered pragmatic trials embedded in Indian service settings, and economic evaluation reflecting household expenditure.